2018
DOI: 10.1177/0886260518799457
|View full text |Cite
|
Sign up to set email alerts
|

How Thai Women Manage Living in the Context of Intimate Partner Violence

Abstract: Although there is literature that describes coping strategies of women who experience intimate partner violence (IPV), the definitions of common coping strategies and the two-dimensional model of coping styles (emotion-or problem-focused) may not fully delineate how these women manage their day-to-day lives. Using an Interpretive Description method and feminist standpoint principles, in-depth interviews were conducted with 40 Thai women regarding how they managed living in the context of IPV. Data were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Feelings of helplessness may contribute to the associations between IPV victimization and depression in adulthood (Bargai et al, 2007). However, research has shown that abused women use more emotion-focused coping strategies to reduce their stressors and that coping is linked to increased risk of depression (e.g., Choi et al, 2015; Khodabakhshi-Koolaee et al, 2018; Thananowan et al, 2018). In addition, social stigmatization can directly discourage abused women from seeking medical help and create difficulties in obtaining social and emotional support (Štulhofer et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Feelings of helplessness may contribute to the associations between IPV victimization and depression in adulthood (Bargai et al, 2007). However, research has shown that abused women use more emotion-focused coping strategies to reduce their stressors and that coping is linked to increased risk of depression (e.g., Choi et al, 2015; Khodabakhshi-Koolaee et al, 2018; Thananowan et al, 2018). In addition, social stigmatization can directly discourage abused women from seeking medical help and create difficulties in obtaining social and emotional support (Štulhofer et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Disclosing IPV to anyone or seeking help from others would bring shame to a woman and her family. Thus, many of the abused Thai women remain silent about their experiences of violence (Thananowan et al, 2018), resulting in underreporting of IPV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Victims of IPV may keep silent and face a substantial amount of shame and stigma, making it difficult for them to seek help from outsiders until their health or overall situation becomes severe. 23 As a result, IPV might undermine a woman’s ability to access health care services and disclose the abuse to someone. In practice, though, few clinical settings in Thailand support routine screening or assessment for IPV, and most Thai providers do not screen for IPV.…”
Section: Discussionmentioning
confidence: 99%
“…Drinking serves as a symbol of masculine gender identity, and alcohol is used as a tool to justify men's IPV and violence against other family members [19]. Studies on domestic violence in Thailand in the literatures are all in the context of IPV in married or cohabitating heterosexual relationships [4,[20][21][22]. The prevalence of lifetime experience of IPV in Thailand varied from 16% in a survey of 1444 women in 4 provinces in 4 regions [20] to 27% in a survey of 580 women in seven Bangkok slums [4].…”
Section: Introductionmentioning
confidence: 99%